Correction of Biapical Tibial Deformity by True Spherical Osteotomy, Modified Circular External Skeletal Fixation and Distraction Osteogenesis - Walmsley, Darby; Fitzpatrick, Noel; Black, Cameron (VCOT Open, 2019)
Objectives The aim of this study was to describe a case of biapical tibial deformity as a result of premature distal physeal closure corrected by true spherical osteotomy, circular external skeletal fixation and distraction osteogenesis.Methods A 6-month-old male Labrador Retriever was presented for the evaluation and treatment of angular limb deformity of the left pelvic limb, with radiography and computed tomography revealing a multiplanar, biapical, compensatory tibial growth deformity, with marked distal tibial recurvatum and varus. A true spherical osteotomy was performed at the distal tibial centre of rotation of angulation (CORA), allowing for correction of the deformity in three planes, with a transverse osteotomy performed at the most proximal CORA. A circular external skeletal fixator was applied and distraction osteogenesis performed at the transverse osteotomy. Latency, distraction osteogenesis, and consolidation were performed over a 113-day period.Results At frame removal, tibial length discrepancy improved from 16.8% to 0.6% and frontal plane varus angulation improvement from 20° to 5°, when compared with the contralateral limb. Long-term evaluation revealed a satisfactory clinical and cosmetic outcome, judged by the clinician and owners, with force plate analysed symmetry index of the pelvic limb within reported normal limits.Clinical significance To our knowledge this is the first case report illustrating the value of true spherical osteotomy for the treatment of an angular limb deformity when performed in combination with distraction osteogenesis in a canine pelvic limb.
Keywords: angular limb deformity; true spherical osteotomy; distraction osteogenesis; external skeletal fixation